2012
DOI: 10.1371/journal.ppat.1002578
|View full text |Cite
|
Sign up to set email alerts
|

Stage Specific Assessment of Candida albicans Phagocytosis by Macrophages Identifies Cell Wall Composition and Morphogenesis as Key Determinants

Abstract: Candida albicans is a major life-threatening human fungal pathogen. Host defence against systemic Candida infection relies mainly on phagocytosis of fungal cells by cells of the innate immune system. In this study, we have employed video microscopy, coupled with sophisticated image analysis tools, to assess the contribution of distinct C. albicans cell wall components and yeast-hypha morphogenesis to specific stages of phagocytosis by macrophages. We sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
173
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 129 publications
(190 citation statements)
references
References 47 publications
(65 reference statements)
15
173
0
2
Order By: Relevance
“…More importantly, the method described enables differential analysis of the individual stages of phagocytosis. We have, for example, shown that changes in overall uptake of C. albicans glycosylation and morphogenesis mutants by macrophage cell lines and primary macrophages can be either a consequence of changes in macrophage migration towards target cells or rate of engulfment once cell-cell contact is established 7 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…More importantly, the method described enables differential analysis of the individual stages of phagocytosis. We have, for example, shown that changes in overall uptake of C. albicans glycosylation and morphogenesis mutants by macrophage cell lines and primary macrophages can be either a consequence of changes in macrophage migration towards target cells or rate of engulfment once cell-cell contact is established 7 .…”
Section: Discussionmentioning
confidence: 99%
“…However, target size is an important determinant for feasibility, as image analysis becomes increasingly difficult with a reduction in target cell size. Sophisticated image analysis software is essential for rapid video microscopy analysis, and this should be coupled with appropriate bioinformatics support to facilitate the generation of algorithms to study migration of individual cells and entire cell populations 7 . Live-cell video microscopy in combination with sophisticated image analysis software for the minute-by-minute analysis of migration and individual macrophage-C.albicans interactions, provides unique insight into the complexity of C. albicans phagocytosis by macrophages.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Its prevalence may be growing, however due to the use of technologies that enable continuous monitoring of biological processes. One recent example of activity-based mechanistic evidence comes from the article, "Stage Specific (Lewis, Bain et al 2012). Supporting video S3 from this article uses video microscopy to show a macrophage moving toward and subsequently engulfing a C. albicans yeast cell.…”
Section: Rethinking Mechanistic Evidence For the Health Sciencesmentioning
confidence: 99%
“…As taxas de fagocitose encontram-se dentro do descrito para este modelo, sendo que com trinta minutos de interação, já era possível observar taxas de fagocitose próximas à máxima decorrente de maiores tempos de cocultivo, conforme descrito na literatura (Lewis et al, 2012). A fagocitose é um fenômeno importante pois várias vias de transdução de sinal dependem da internalização da célula fúngica para serem ativadas (Bourgeois et al, 2011;Kagan et al, 2008 Choi et al, 2014;Longo et al, 2014;Lowe et al, 2014;Tierney et al, 2012).…”
Section: Caracterização Das Bases Moleculares Da Suscetibilidade a Cunclassified